Estimating the Lock-in Effects of Switching Costs from Firm-Level Data - Gábor Kézdi; Gergely Csorba (Hungarian Academy of Sciences, Institute of Economics, 2011)
This paper proposes a simple method for estimating the lock-in effects of switching costs from firm-level data. We compare the behavior of already contracted consumers to the behavior of new consumers as the latter can serve as contrafactual to the former. In panel regressions on firms' incoming and quitting consumers, we look at the differential response to price changes and identify the lock-in effect of switching costs from the difference between the two. We illustrate our method by analyzing the Hungarian personal loan market and find strong lock-in effects.
Keywords: C33; D12; L13; 330; switching costs; lock-in; panel data; Wechselverhalten; Konsumentenverhalten; Panel; Kreditgeschäft; Ungarn